1999
DOI: 10.1159/000027404
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Intravitreal Application of Ciprofloxacin in Rabbits

Abstract: Background: Ciprofloxacin (CFLX) is a fluoroquinolone antibiotic with a broad antimicrobial spectrum. This study was performed to examine the retinal toxicity of free and liposome-incorporated CFLX in rabbit eyes after intravitreal injection. Materials and Methods: Free CFLX in doses of 100, 250, 500, 1,000 and 2,000 µg was injected into the midvitreous of rabbit eyes (n = 28). To prolong the intravitreal antibacterial level, CFLX was incorporated into multilamellar liposomes: 0.1 ml of this suspension (≙ 273.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Regarding intravitreal use, ciprofloxacin has not been associated with toxicity at the therapeutic levels of 100-500 g in rabbits, and significant retinal damage has been observed only at 2 mg [28] .…”
Section: Quinolonesmentioning
confidence: 99%
“…Regarding intravitreal use, ciprofloxacin has not been associated with toxicity at the therapeutic levels of 100-500 g in rabbits, and significant retinal damage has been observed only at 2 mg [28] .…”
Section: Quinolonesmentioning
confidence: 99%
“…The safety of ocular (topical and/or intra-vitreal) administration of ofloxacin [10][11][12], ciprofloxacin [10], evofloxacin [13], norfloxacin [14], trovafloxacin [15], moxifloxacin [16] and garenoxacin [17] has been investigated, and the results lead to the conclusion that FQs show varied affinity for retinal tissues and there are a marked differences among compounds for safe doses for ocular administration.…”
Section: Introductionmentioning
confidence: 99%
“…Cochereau-Massin et al [24] found toxicity with intravitreal injection of pefloxacin 1.6 mg. Norfloxacin and ciprofloxacin exhibited toxicity at doses higher than 2 mg [25,26]. In our study, GRE showed no funduscopic or histologic alterations after intraocular injection of 800 Ìg GRE.…”
Section: Discussionmentioning
confidence: 42%